2022
DOI: 10.1155/2022/6154885
|View full text |Cite
|
Sign up to set email alerts
|

PPP Financing Model in the Infrastructure Construction of the Park Integrating Artificial Intelligence Technology

Abstract: The objective is to study the application of the Public-Private-Partnership (PPP) financing model in the infrastructure construction of the park. By analyzing the operation model of the PPP financing model, combined with the Artificial Intelligence (AI) technology, the theory mechanism that digital infrastructure construction and Internet use affect the quality of employment is proposed. Based on the selection theory of the PPP model for infrastructure construction projects in industrial parks, the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Regarding the control variables of the models, the contribution of GOVERNMENT EX-PENDITURE in strengthening the capacity of governments to implement artificial intelligence is confirmed and demonstrates a positive relationship with dependent variable: the higher the volume of government spending, the higher the government's readiness in artificial intelligence. The results confirm the general assumptions from previous literature (Wang & Cui, 2022;Bredt, 2019;Duan et al, 2019;Bose et al, 2007) and the resorts of such an interdependence are related to the innovative and relatively expensive technical character of the state's investments in the artificial intelligence infrastructure and software for the public services. Also, the personnel needed to develop and manage informatic applications and infrastructure based on artificial intelligence leads to significant government spending.…”
Section: Instrumental-variables Regressionssupporting
confidence: 89%
See 2 more Smart Citations
“…Regarding the control variables of the models, the contribution of GOVERNMENT EX-PENDITURE in strengthening the capacity of governments to implement artificial intelligence is confirmed and demonstrates a positive relationship with dependent variable: the higher the volume of government spending, the higher the government's readiness in artificial intelligence. The results confirm the general assumptions from previous literature (Wang & Cui, 2022;Bredt, 2019;Duan et al, 2019;Bose et al, 2007) and the resorts of such an interdependence are related to the innovative and relatively expensive technical character of the state's investments in the artificial intelligence infrastructure and software for the public services. Also, the personnel needed to develop and manage informatic applications and infrastructure based on artificial intelligence leads to significant government spending.…”
Section: Instrumental-variables Regressionssupporting
confidence: 89%
“…AI's application in government spans various domains: in Public Services, it could automate tasks like application processing and inquiry handling; in Policy and Decision-making, it could analyze extensive datasets for policy shaping; in Law Enforcement and Public Safety, technologies like facial recognition and predictive analytics could augment safety efforts; in Infrastructure and Resource Management, AI could assist in resource management and infrastructure planning (Wang & Cui, 2022); and in Healthcare, AI could improve public health outcomes by analyzing medical data for disease detection and treatment optimization (Gomes de Sousa et al, 2019).…”
Section: Interaction Between Government Ai and Brain Drainmentioning
confidence: 99%
See 1 more Smart Citation
“…The EU's approach to PPPs is based on the European Commission's PPP guidelines, which emphasize the need for transparency and competition in the procurement process. Practical studies of PPPs in the energy sector in other countries provide insight into best practices (Vagliasindi 2012b;Vagliasindi 2012c;Vagliasindi 2013;Wang and Cui 2022), which can be applied in Ukraine. For example, the literature states (FC-World Bank 2014) that a successful PPP requires clear project goals, clearly defined risk allocation, and a solid financial structure.…”
Section: New Opportunities For Public-private Partnership In the Ener...mentioning
confidence: 99%
“…Liu [9] discussed the characteristics of the commonly used project management model and the new innovative model. Wang and Cui [10] explored the application of public-private-partnership (PPP) business model in the infrastructure construction of industrial parks, and Liu [11] found that the introduction of build-operate-transfer (BOT) mode is important for environmental protection and pollution control in industrial parks. In recent years, some scholars began to try to explore the construction mode of data platform.…”
Section: Introductionmentioning
confidence: 99%